Study of the Effect of Thermal Diffusivity on the Unstable Temperature distribution through a Low Thermal Conductivity / دراسة تأثير الانتشارية الحرارية على توزيع درجات الحرارة غير المستقرة خلال الجدران ذات التوصيل الحراري المنخفض باستخدام برنامج الانسز (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Although there have been a large number of studies that Searched in  the relationship between the thermal properties of the materials and the rate of unstable heat transfer, We did not note the existence of comprehensive charts and tables showing the relationship between different materials under different thermal conditions.            This study is an attempt to conceptualize the general relationship between the thermal diffusivity of any material and its thermal behavior when subjected to any thermal conditions (∆T) in the unstable state. And benefit from the results of this study to develop general data that make it easier for the concerned engineers to visualize the thermal behavior of the materials at any thermal conditions.            The study model is to place a constant thermal load (60 oC) on the outside of a wall of thickness (10 cm) in a room with a constant temperature at (20 oC). In this study a range of lightweight materials with low thermal conductivity was used. The Ansys program was also used to implement this study.            The results showed a positive correlation between thermal diffusivity and temperature rise. The study also showed the cooling effect of another sides of the wall on reducing the heating rate, especially for the low thermal diffusivity materials. Through data and equations obtained by research We can predict thermal behavior  For materials with thermal diffusivity  Confined between (8E-7 - 2.00E-9(m2/sec)) When applying the applied thermal conditions in the research.